2018
DOI: 10.1530/eje-17-0496
|View full text |Cite
|
Sign up to set email alerts
|

Changes in regional body fat, lean body mass and body shape in trans persons using cross-sex hormonal therapy: results from a multicenter prospective study

Abstract: CHT causes a more feminine body fat distribution and a lower WHR in transwomen and a more masculine body fat distribution with a lower hip circumference in transmen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
122
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 17 publications
10
122
1
Order By: Relevance
“…Peripherally, the interaction with estradiol may explain the different effects of T on women metabolism [ 92 ]. Additionally, cross-sex hormonal therapy of male-to-female transsexuals increases the amount of subcutaneous adipose tissue accrual relative to intra-abdominal adipose tissue whereas more masculine body fat distribution with a lower hip circumference has been observed in trans males [ 93 ].…”
Section: Sex Hormones In Endocrine Gender-related Differencesmentioning
confidence: 99%
“…Peripherally, the interaction with estradiol may explain the different effects of T on women metabolism [ 92 ]. Additionally, cross-sex hormonal therapy of male-to-female transsexuals increases the amount of subcutaneous adipose tissue accrual relative to intra-abdominal adipose tissue whereas more masculine body fat distribution with a lower hip circumference has been observed in trans males [ 93 ].…”
Section: Sex Hormones In Endocrine Gender-related Differencesmentioning
confidence: 99%
“…Trans women (birth-assigned males, female identity) receive estrogens to induce feminization, resulting, for example, in breast growth (1) and changes in body composition. (2) Trans men (birth-assigned females, male identity) are treated with testosterone, which, among others, stimulates lowering of the voice (3) and growth of body hair. (4) Sex steroids also play important roles in the acquisition and homeostasis of bone.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies from the ENIGI cohort have reported that estradiol concentration did not predict breast development or more feminine changes in body composition in transfeminine individuals. 2,17 However, higher estradiol concentrations have been associated with a higher lumbar spine bone mineral density. 18 Ultimately, the best assessment of hormonal efficacy is the clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…This results in development of feminine physical characteristics, including softening of skin, a decrease in facial and body hair growth, breast development, and changes in body composition manifested by body fat redistribution and decreased muscle mass. 1,2 Estradiol is most commonly administered via the oral or transdermal route, 3 and oral estradiol valerate is the most common first-line feminising treatment in clinicians experienced in transgender healthcare in Australia. 4 Several consensus guidelines give recommendations for estradiol concentrations to allow titration of estradiol therapy.…”
Section: Introductionmentioning
confidence: 99%